Geologia, petrografia, geoquímica e química das piritas associadas às ocorrências de cobre hidrotermal da porção oeste da província Borborema - Rodrigues, Thainara Freires (2023)
The Eopaleozoic transtensional setting in Borborema Province displays many favorable structures and host rocks for the formation of mineral deposits. Previous studies describe the potential occurrence of copper deposits associated to iron oxides in different rift basins along Borborema Province, with special emphasis to those associated to quartz-hematite breccias in the basins of Carnaubinha/São Bento (Piauí State) and Jaibaras/Cococi (Ceará State). Similarities in mineralization style, tectonic setting and hydrothermal alteration suggest that these occurrences are part of a single continental scale mineral system. To confirm such hypothesis, it is necessary to compare the hydrothermal alteration styles and geochemistry of the different mineralized areas. This MSc research is intended to provide a detailed characterization of the copper occurrences in Carnaubinha and São Bento Eopaleozoic basins and related basement (Pio IX region), in the southwestern portion of Borborema Province, defining their associated hydrothermal alteration relationships. To address such purposes, petrological, geochemical and mineral chemistry analyses were performed, aiming the establishment of a mineral system model for the key localities within the geodynamic framework of the Borborema Province. Petrographic studies allowed the characterization of the hydrothermal alteration in the basement rocks of Orós Group and São Nicolau complex. They consist of Albite, K-feldspar, Epidote, Chlorite alterations, silicification and silica-hematite alteration, where the last two phases are associated to copper occurrences. They occur as veins and stockworks, or pervasively substituting the protolith. In Carnaubinha basin, the alteration consists of k-feldspar, epidote and chlorite, occurring predominantly as structurally controlled veins, while silicification and silica-hematite alteration occur as veins, stockworks and pervasively in the conglomerates, being also associated to the presence of copper minerals. In São Bento basin, silicification is the main alteration type and occur as veins and stockworks; hematite alteration occurs as dispersive hematite formation in the conglomerate matrix and clasts, and associated to the silicification in veins sets; similarly, chlorite alteration occurs in the matrix, and as late veins overprinting the silicification; sulfide alteration is represented by abundant pyrite, while crystals are deformed and overprinted by silicification. Principal component analyses of the geochemistry results for the basement samples showed that epidote-chlorite alteration is characterized by higher CaO, Na2O3 and MgO associated to La, Ce, Hf, Zr, Y, Sr and Th, while k-feldspar have K2O, Al2O3 and Na2O3 gains associated to Rb, Sn and Nb. While silica-hematite alteration breccias are SiO2 and Fe2O3 enriched associated to Pb, W, Sb, W, Sb, V, Ba, Mo and Co. When associated to copper occurrences, they show Cu, Bi, Ag, Se, Te and As gains. Silica-alteration breccias associated to copper occurrences show higher Cr and As gains. MnO, TiO2, U and Hg occur in all copper breccias. Carnaubinha basin conglomerate breccias with k-feldspar and epidote-chlorite alterations have CaO, Na2O3 enrichment associated to Ga, La, Ce, Ti, Sr, Mn, Y, Li and Ta. Silica-alteration volcanoclastic breccias are enriched in Al2O3, Na2O and K2O, and Cs, Sc, Nb, Th, Sn and Rb. The silicified copper rich conglomerate is linked with CaO, MgO, TiO2 and MnO, besides Be, Cd, Zn, Li, Ni and P. Finally, the basin silica-hematite breccias has Se, Ag, Cu, As, Te and Bi gains. Pyrite chemistry analyses showed the basement pyrites main trace elements are Co, Ni, Hg, Ag, As, Mn, Se and Zn. Carnaubinha basin silica-hematite breccia is characterized by Co, Cu, Se, Hg Ni, Te, As and Mn trace elements, while silica-sulfide breccia results show a similar enrichment in Co, followed by Ni, Hg, As, Se, Mn, Te, Zn, Ag and Cu. São Bento basin pyrite main trace elements are Hg, Cu, Co, Ag, Te, Zn, Mn and Se. Carnaubinha and basement breccias have high Co/Ni rations, majorly > 10 ppm, while for São Bento basin the ratios are predominantly < 2 ppm. Similarities in alteration styles and paragenetic sequence affecting Carnaubinha basin and basement rocks and geochemistry results demonstrate a similar signature for these alterations and copper occurrences indicate that these are part of a single hydrothermal alteration system. In São Bento basin, alterations are incipient and the hydrothermal system is less evolved. Similarly, the pyrite chemistry results indicate that a higher magmatic- hydrothermal source of fluids for Carnaubinha basin and basement breccias, while São Bento pyrite indicate a sedimentary source with minor hydrothermal contribution. Compiled results indicate that the similar hydrothermal system affected in different stages the rocks of Orós mobile belt, its basement, and eopaleozoic basins.